A Cognitive-Behavioral Counseling Model Using Self-Management Techniques to Enhance Career Maturity - I Komang Cahya Krisna; Ni Ketut Suarni; I Ketut Gading (Department of Guidance and Counseling, FIP, Undiksha, 2026)
Low career maturity among students remains a serious problem characterized by a lack of understanding of self-potential, career goals, and weak ability to make career decisions independently. This study aims to analyze the tendency of students' career choice profiles and the effectiveness of the cognitive behavioral counseling model with self-management techniques in improving the career maturity of grade XI students. This study used a quasi-experimental design with a nonequivalent pretest-posttest control group design. The research subjects consisted of 64 students divided into an experimental group and a control group. The research instrument was a career maturity questionnaire that had been tested for validity and reliability. The results showed that the level of career maturity of students before being given treatment was in the moderate category, which indicated that most students still experienced confusion in determining career direction and future planning. After being given treatment in the form of cognitive behavioral counseling with self-management techniques, the results of the independent sample t-test were obtained with a significance value of 0.000 (<0.05). This indicates a significant difference between the experimental group and the control group. The experimental group experienced an increase in the average post-test score compared to the control group. In conclusion, the cognitive-behavioral counseling model with self-management techniques is effective in improving the career maturity of eleventh-grade students. The implication is that the cognitive-behavioral counseling model with self-management techniques can be used as an alternative, effective guidance and counseling service to improve students' career maturity.